2016
DOI: 10.1186/s13071-016-1914-6
|View full text |Cite
|
Sign up to set email alerts
|

Size, sounds and sex: interactions between body size and harmonic convergence signals determine mating success in Aedes aegypti

Abstract: BackgroundSeveral new mosquito control strategies will involve the release of laboratory reared males which will be required to compete with wild males for mates. Currently, the determinants of male mating success remain unclear. The presence of convergence between male and female harmonic flight tone frequencies during a mating attempt have been found to increase male mating success in the yellow fever mosquito, Aedes aegypti. Size has also been implicated as a factor in male mating success. Here, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 47 publications
3
44
1
Order By: Relevance
“…Adult size, which can be influenced by larval food availability and temperature exposure, has been found to influence mosquito WBFs, with larger individuals displaying higher WBFs in some studies (Costello 1974, Wekesa et al 1998, Cator et al 2010. To determine the ability of the ultrasonic system to detect changes in WBF related to differences in body size, we reared cohorts under different feeding regimes to generate ''small'' and ''large'' sized males and females following the methods of Cator and Zanti (2016). In short, cohorts of 500 1st instars were subjected to either ''high'' or ''low'' food treatments to produce large or small adults.…”
Section: Size Assaysmentioning
confidence: 99%
“…Adult size, which can be influenced by larval food availability and temperature exposure, has been found to influence mosquito WBFs, with larger individuals displaying higher WBFs in some studies (Costello 1974, Wekesa et al 1998, Cator et al 2010. To determine the ability of the ultrasonic system to detect changes in WBF related to differences in body size, we reared cohorts under different feeding regimes to generate ''small'' and ''large'' sized males and females following the methods of Cator and Zanti (2016). In short, cohorts of 500 1st instars were subjected to either ''high'' or ''low'' food treatments to produce large or small adults.…”
Section: Size Assaysmentioning
confidence: 99%
“…Morphological variation of somatic and genital traits may have significant impact on mating success in many animal groups (Langerhans et al, 2005;Ponlawat and Harrington, 2009;Cator and Zanti, 2016). Somatic traits are under the influence of precopulatory sexual selection (Jones and Ratterman, 2009), while sexual traits can be subjected to both pre-and postcopulatory selection (Polihronakis, 2006;Kamimura, 2014;Simmons, 2014).…”
Section: Morphological Variation Of Gonopods (Promeres and Opisthomermentioning
confidence: 99%
“…The existence of such patterns of morphological variability may lead to intrasexual variation in mating tactics and/ or mating success. Indeed, many studies have shown that overall body size Austad, 1990, 1994;Wedell, 1991;Simmons et al, 1996;Wenninger and Averill, 2006;Pavković-Lučić et al, 2009;Helinski and Harrington, 2011;Cator and Zanti, 2016) correlates to male mating and fertilisation success. Additionally, it has been shown that variation in characteristics of mating sequences, such as copulation duration, may be a factor that influences male fertilisation success (Simmons and Parker, 1992;Arnqvist and Danielsson, 1999a;AndrĆ©s and Cordero Rivera, 2000;Jones et al, 2006).…”
Section: Introductionmentioning
confidence: 99%